PENGARUH LINGKUNGAN PENDIDIKAN KELUARGA DALAM PEMBENTUKAN KARAKTER ANAK PERSPEKTIF ISLAM DALAM SURAT THAHA AYAT 132 DAN AL-HAJJ AYAT 41 - Dina Taflilah; Annisa Febrinandini (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2023)
This article discusses the influence of the family educational environment on the formation of a child's character from an Islamic perspective. The author took several verses related to the title including Q. S. Thaha verse 132 and Q. S. al-Hajj verse 41 which explains that the family is the first source for children in basic teaching of the Islamic religion and the formation of a good character in accordance with Islamic religious rules. This article aims to find out what influence the family environment has on the formation of a child's character within the scope of Islam. Methodology This research was carried out through library research and previous studies by reviewing research results that have been published in related journals in electronic media. The results of the literature study show that the family environment is very influential in character formation because it is the first and main place of education, both physically and psychologically. The conclusion of this article is that the family educational environment influences the formation of a child's character within the scope of Islam where children receive the main educational provisions, both general and religious, through the role of parents and the family educational environment.